Compliance and persistence with Alzheimer's disease treatment: a retrospective analysis of multiregional hospital databases in Thailand - Kongpakwattana, Khachen; Dilokthornsakul, Piyameth; Dejthevaporn, Charungthai; Pattanaprateep, Oraluck; Chaiyakunapruk, Nathorn (Journal of medical economics, 2019)
Due to the lack of studies evaluating compliance or persistence with Alzheimer's Disease (AD) treatment outside High-Income Countries (HICs), this study aimed to assess compliance, persistence, and factors associated with non-compliance and non-persistence by utilizing existing "real-world" information from multiregional hospital databases in Thailand. Study subjects were retrospectively identified from databases of five hospitals located in different regions across Thailand. AD patients aged ≥60 years who were newly-prescribed with donepezil, galantamine, rivastigmine, or memantine between 2013 and 2017 were eligible for analysis. The Medication Possession Ratio (MPR) was used as a proxy for compliance, while the Kaplan-Meier survival analysis was employed to estimate persistence. Logistic and Cox regressions were used to assess determinants of non-compliance and non-persistence, adjusted for age and gender. Among 698 eligible patients, mean (SD) MPR was 0.83 (0.25), with 70.3% of the patients compliant to the treatment (having MPR ≥ 0.80). Half of the patients discontinued their treatment (having a treatment gap >30 days) within 177 days with a 1-year persistence probability of 21.1%. The patients treated in the university-affiliated hospital were more likely to be both non-compliant (OR = 1.71; 95% CI = 1.21-2.42) and non-persistent (HR = 1.33; 95% CI = 1.12-1.58). In addition, non-compliance was higher for those prescribed with single AD treatment (OR = 2.52; 95% CI = 1.35-4.69), while non-persistence was higher for those unable to reimburse for AD treatment (HR = 1.34; 95% CI = 1.11-1.62). By using retrospective databases, a difficulty in validating whether the medications are actually taken after being refilled may over-estimate the levels of compliance and persistence. Meanwhile, possible random coding errors may under-estimate the strength of association findings. This study reveals the situation of compliance and persistence on AD treatment for the first time outside HICs. The determinants of non-compliance and non-persistence underline key areas for improvement.